The Winning New Issues: A Case Study - Howard M. Schilit; W. Keith Schilit (Journal of Small Business Finance, 1992)
Why do some early stage ventures perform remarkably well while others fail? Is there a fairly accurate way to predict which emerging growth business will become a high performing success story and which a low performing disaster? Is there a way for investors to increase the likelihood of investing in “winners” and decrease the likelihood of investing in “losers”? These are the central questions addressed in this article.
Keywords: G32; G12; 650; New Issues